STARSMILE APP TO IMPROVE KNOWLEDGE OF DENTAL AND ORAL HEALTH AND TOOTH BRUSHING BEHAVIOR - Satria Yandi; Restu Putri Purwany Susilo; Tiara Rahma Sabilla; Dwi Anggun Vidiza Putri (Universitas Baiturrahmah, 2026)
Introduction: Poor oral hygiene is a common problem among preschool children and is influenced by parental guidance and socioeconomic factors. Objective: This study aimed to evaluate the effectiveness of the StarSMILE App, a game-based educational tool, in improving tooth brushing knowledge and behavior among preschool children and their parents. Methods: This study employed a Level 3 Research and Development (R&D) approach using the ADDIE model and systematic validation by subject matter, media, and learning experts. Five parents and children tested the StarSMILE App to determine user-level validation. Results: The StarSMILE App was proven to be suitable for use after passing expert validation and user trials. The assessment details showed 89% approval from media experts, 85% approval from subject matter experts, and 84% approval from learning experts. Positive feedback was also received from users, with a very high feasibility rate of 91.2%.